Shape-persistent macrocycles - Self-assembly reactions and characterization by hyperpolarized 129Xe NMR spectroscopy - Campbell, Katie; Ooms, Kristopher J.; Ferguson, Michael J.; Stang, Peter J.; Wasylishen, Roderick E.; Tykwinski, Rik (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2011)
The use of three shape-persistent, conjugated macrocycles 2a-2c as ligands for self-assembly reactions is described. The macrocycles have been characterized through a combination of spectroscopic analyses and, for compounds 2b and 2c, X-ray crystallographic analysis. Whereas the reaction of 2a with the cis-Pt(II) species 3 successfully provides the porous solid 4a, the analogous reaction of 2b and 2c with 3 leads only to mixtures of products. The application of continuous-flow hyperpolarized Xe NMR spectroscopy to investigate the solid-state pores of macrocycles 2b and 2c and the supramolecular complex 4a as a function of temperature is described. All three species show permanent porosity upon removal of co-crystallized solvent molecules. Using trends in the Xe chemical shifts and temperature-dependent dynamics of Xe atoms in the solids, information is obtained on the nature of the pores in these systems. Using the Xe NMR data for complex 4a, the effective heat of adsorption (δH ) was calculated to be ∼29 kJ mol. © 2011 Published by NRC Research Press.